Musica viva in schola XXVII. Sborník konferenčních příspěvků - Brunner, Georg (Masaryk University Press, 2021)
Title in English: Musica viva in schola XXVII. The proceeding from the jubilee 30th international music-educational conference Musica viva in schola continues the tradition of publishing MVIS conference papers from previous years. The contributions respond to current issues in music education and the arts and culture, including modern approaches in education and research projects. In addition to the above, the current year also focuses on musical traditions in music education. Authors include academics and researchers, as well as music didactics, practitioners, and representatives of national and international music education societies.